2020
DOI: 10.21203/rs.2.21688/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resveratrol can enhance osteogenic differentiation and mitochondrial biogenesis from human periosteum-derived mesenchymal stem cells

Abstract: Background Osteoporosis is a metabolic bone disorder that leads to low bone mass and microstructural deterioration of bone tissue and increases bone fractures. Resveratrol, a natural polyphenol compound, has pleiotropic effects including anti-oxidative, anti-aging, and anti-cancer effects. Resveratrol also has roles in increasing osteogenesis and in up-regulating mitochondrial biogenesis of bone-marrow derived mesenchymal stem cells (BM-MSCs). However, it is still unclear that resveratrol can enhance osteogeni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This implies an early stage of the osteogenesis process. Our findings are consistent with the increased mitochondrial biogenesis that occurs during osteogenic differentiation of mesenchymal stem cells 35–37 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This implies an early stage of the osteogenesis process. Our findings are consistent with the increased mitochondrial biogenesis that occurs during osteogenic differentiation of mesenchymal stem cells 35–37 …”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that mitochondrial biogenesis increases during the osteogenesis process, for example, osteogenic differentiation of mesenchymal stem cells 35–37 . Therefore, we examined the gene expression of mitochondrial transcription factor A (mtTFA) and mitochondrial DNA polymerase γ (Polg).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations